Polusi Udara dalam Ruangan dan Kondisi Kesehatan: Analisis Rumah Tangga Indonesia - A’yun, Indanazulfa Qurrota; Umaroh, Rodhiah (UI Scholars Hub, 2022)
Indoor air quality is an important factor for human health because indoor air pollution has a more dangerous impact compared to outdoor air pollution. This study aims to analyze the impact of the use of cooking fuel as a determinant of indoor pollution quality on the health conditions of household members. This study uses Indonesian Family Life Survey (IFLS) 5 data and the instrumental variable method. The results of this study indicate that the use of cooking fuel has impacts on cough, fever and diarrhea especially for individuals at the age of more than 21 years.